1985
DOI: 10.1159/000466385
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of Human Platelets Using 6% Dimethyl Sulfoxide and Storage at -80°C

Abstract: Platelet studies were done in healthy male volunteers and in thrombocytopenic patients. Some of the platelets used in the study were isolated by mechanical apheresis using either the Haemonetics blood processor 30, the IBM blood processor 2997 or the Fenwal CS-3000 blood processor before freezing. Other platelets were isolated from individual units of whole blood and pooled before freezing. The platelets were frozen with a 6% cryoprotectant (DMSO) in a polyvinylchloride (PVC) plastic bag or a polyolefin plasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…In addition to the enhanced recovery of circulating platelets, an important consequence of the use of ThromboSol is the ability to reduce the requirement for DMSO as a cryoprotectant. Previous studies testing the use of reduced concentrations of DMSO during infusion indicated that the recipients showed no adverse effects, even following a 10‐year period (Handin & Valeri, 1972; Lazarus et al , 1981; Melaragno et al , 1985; Spector et al , 1977). The development of a cryopreservation system that contains transfusable components would eliminate both the damaging effects of the wash step and the need to break the closed system.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In addition to the enhanced recovery of circulating platelets, an important consequence of the use of ThromboSol is the ability to reduce the requirement for DMSO as a cryoprotectant. Previous studies testing the use of reduced concentrations of DMSO during infusion indicated that the recipients showed no adverse effects, even following a 10‐year period (Handin & Valeri, 1972; Lazarus et al , 1981; Melaragno et al , 1985; Spector et al , 1977). The development of a cryopreservation system that contains transfusable components would eliminate both the damaging effects of the wash step and the need to break the closed system.…”
Section: Discussionmentioning
confidence: 98%
“…This loss of in vitro functional activity is also reflected in the cryopreserved platelets' in vivo circulatory parameters (Daly et al , 1979; Handin & Valeri, 1972; Kim & Balduini, 1974; Melaragno et al , 1985; Schiffer et al , 1976; Spector et al , 1977). Following infusion, the recovery of 51 Cr‐labelled cryopreserved platelets ranges from 30% to 40% as assessed in multiple studies (Handin & Valeri, 1972; Melaragno et al , 1985; Valeri, 1974).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers are experimenting by treating platelets with dimethyl sulfoxide and freezing them in liquid nitrogen 9,10 . Cryo‐preservation of platelets extends the shelf life of platelets to 1 year but requires extensive washing and processing to remove the cryoprotective agents 11 . Another approach to platelet preservation has been to lyophilize the platelets.…”
mentioning
confidence: 99%
“…Recovery post‐thaw is approximately 75% and after transfusion into normal volunteers, in vivo platelet recovery at 1 h is approximately 33% with a platelet survival thereafter of about 8 d (Melaragno et al , 1985). Cryopreserved platelets acquire a variety of morphological and functional defects in vitro (Spector et al , 1977; Shepherd et al , 1984; Melaragno et al , 1985) but are haemostatically effective in vivo (Schiffer et al , 1978; Melaragno et al , 1985). In one recent study, cryopreserved platelets were reported to be more effective in decreasing blood loss in cardiopulmonary bypass surgery than standard liquid stored platelets (Khuri et al , 1999).…”
Section: Novel Platelet Productsmentioning
confidence: 99%